Plan de marketing para Datilbar - Mucha Roque, Mariano Manuel (2021)
This thesis was carried out with the objective of carrying out and studying a marketing plan on Datilbar for the Ecoachual company, in order to capture the studies acquired by the researcher in his university career and to serve as a bibliographic reference for future research. A descriptive methodology, with a mixed approach and a cross-sectional research time horizon, was used. Likewise, qualitative and quantitative results were obtained that helped project the functional aspects of the product and the numerical aspects that made it possible to project the annual demand for 5 years, from 2019 to 2023, which helped to evaluate the medium-term profitability of Datilbar. The conclusion was reached that the product has the potential to be acquired by its target in the Lima market.